2018
DOI: 10.1071/cp17418
|View full text |Cite
|
Sign up to set email alerts
|

Screening wild progenitors of wheat for salinity stress at early stages of plant growth: insight into potential sources of variability for salinity adaptation in wheat

Abstract: Wild relatives of wheat have served as a pool of genetic variation for understanding salinity tolerance mechanisms. Two separate experiments were performed to evaluate the natural diversity in root and shoot Na+ exclusion and K+ accumulation, and the activity of four antioxidant enzymes within an extensive collection of ancestral wheat accessions. In the initial screening experiment, salinity stress (300 mm NaCl) significantly increased Na+ concentration in roots and leaves and led to a significant decline in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Information on experimental setup, growth conditions, salinity treatments, and collection of aboveground biomass yield under control (Yp) and saline (Ys) conditions for each seedling plant is in Ahmadi et al. (). Detailed information on the tested genotypes is in Appendix .…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on experimental setup, growth conditions, salinity treatments, and collection of aboveground biomass yield under control (Yp) and saline (Ys) conditions for each seedling plant is in Ahmadi et al. (). Detailed information on the tested genotypes is in Appendix .…”
Section: Methods and Resultsmentioning
confidence: 99%
“…A greenhouse pot experiment was conducted in 2015-2016 at the Crop Production and Breeding Department, Imam Khomeini International University, Qazvin, Iran. Information on experimental setup, growth conditions, salinity treatments, and collection of aboveground biomass yield under control (Yp) and saline (Ys) conditions for each seedling plant is in Ahmadi et al (2018b). Detailed information on the tested genotypes is in Appendix S1.…”
Section: Testing Ipastic Softwarementioning
confidence: 99%
“…Therefore, these new resources can provide an ideal opportunity for producing new varieties. Wild wheats are a valuable source of genes related to water deficit stress and other abiotic and biotic stresses [15,[29][30][31][32]. For example, Aegilops tauschii Coss.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, distribution of this germplasm in the different parts of Iran, suggest that this area is an ideal source of diversity for discovering useful genes to transfer into modern wheat. Several studies reported that T. urartu is an ideal source of genes related to seed quality, tolerance to both biotic [especially for leaf rust and powdery mildew diseases] and abiotic [especially for drought, salinity and cold] stresses tolerance [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%